HUBUNGAN KUALITAS TIDUR DAN STRES TERHADAP KEJADIAN HIPERTENSI PADA PASIEN USIA 15-64 TAHUN DI PUSKESMAS KECAMATAN SAWANGAN KOTA DEPOK TAHUN 2022 - Alma Putri Maulidawati (2023)
Hypertension occurs due to hemodynamic imbalances in the heart and vascular system which increases the hypertension rate in Depok City by 25.8%. In Sawangan Baru and Lama villages, there are 2,916 people or 53.16% who suffer from hypertension. There are many variables that can cause blood pressure to rise, including poor sleep habits and lack of stress management due to various stressors. This study aims to examine sleep quality and stress on the incidence of hypertension at the Sawangan Sub-District Health Center, Depok City in 2022. The method used was quantitative research with a cross-sectional approach, using research instruments in the form of surveys and medical data. Sleep quality was measured by the Pittsburgh Sleep Quality Index (PSQI) and Stress was measured by the Perceived Stress Scale (PSS-10). This study had 44 participants who met the research criteria as respondents. According to the data collected, the majority of respondents (77.3%) had poor sleep quality, while 37 (84.1%) had stress and 34 (77.3%) had hypertension. Fisher Exact alternative test was used to conduct the analysis, which revealed that there was no significant association between sleep quality and the occurrence of hypertension. As for stress and the incidence of hypertension, the p value was 0.004 (p < 0.05) with an odds ratio (RO) value of 16,000 indicating that there is an association between stress and the incidence of hypertension in individuals aged 15 to 64 years with the chance of experiencing the incidence of hypertension 16,000 times greater than respondents who do not experience stress. Increased sympathetic nerve activity has an impact on emotional situations, so that a person is more prone to stress which causes an increase in blood pressure.